Antibacterial activity of jamblang leaf ethanol extract (Syzygium cumini) against the growth of Propionibacterium acnes - Maria Fransiska Priska Yulianti; Anita Lidesna Shinta Amat; Regina Marvina Hutasoit; Prisca Deviani Pakan (Acta Biochimica Indonesiana)
Background: Propionibacterium acnes is a bacterium found on the skin that plays a significant role in acne vulgaris. The inappropriate use of antibiotics can lead to resistance, necessitating the search for alternative therapies from plants with high antibacterial potential. One such plant is jamblang (Syzygium cumini), which has demonstrated antibacterial properties.